Video-Based Health Education For Pregnant Women On Knowledge Of The Hazards Of Cigarette Exposure In Pregnancy At Kandangan Puskesmas - Nurulita Widyazizah; Sari, Reny Mareta (Universitas STRADA Indonesia, 2022)
Exposure to cigarette smoke in pregnant women can lead to risks in pregnancy. The effects of exposure to cigarette smoke in pregnant women are very dangerous because 75% of cigarette smoke will be inhaled by pregnant women and can affect the fetus in the womb, such as premature babies, babies born with low weight. LBW), babies born with defects. The purpose of this study was to examine the effect of health education with videos on the knowledge of pregnant women about the dangers of exposure to cigarette smoke in pregnancy. Method The research design used is quantitative with a quasi-experimental research design with a sampling technique that is accidental sampling. The sample used was part of the population of pregnant women from trimester 1 to trimester 3 who did a pregnancy check (ANC) at the Kandangan Health Center, Kediri Regency and obtained as many as 64 respondents. This data collection tool uses a questionnaire. Data analysis using Wilcoxon test. The results of this study obtained 0.000 < 0.05 there arethe effect of video-based health education on pregnant women on knowledge of the dangers of exposure to cigarette smoke in pregnancy. The results of the pre-test knowledge of pregnant women were 92.1% had less knowledge and after being given the intervention, it was found that 57.9% had sufficient knowledge. It is concluded that the knowledge of pregnant women about the dangers of exposure to cigarette smoke is still inadequate. This happens because the information obtained by pregnant women is still lacking. It is important to provide information to the public, especially pregnant women about the dangers of cigarette smoke.